Intercultural service encounters: a systematic review and a conceptual framework on trust development - Vrontis, Demetris; Leonidou, Erasmia; Christofi, Michael; Kaufmann Hans, Ruediger; Kitchen, Philip J. (My University, 2020)
Purpose: A significant body of research has now been accumulated in the intercultural service encounter (ICSE) literature. However, no study to date has provided scholars and practitioners with a systematic review to map and better understand the ICSE domain. Design/methodology/approach: To fill this gap, the authors systematically review and critically examine the state of academic research on ICSE. Findings: Based on a systematic review of 31 journal articles published over the last two decades, the results illustrate that ICSE research is a vibrant and rapidly growing stream of the broader international business domain, and it is topically and methodologically diverse. This review also identifies significant knowledge gaps related to the adoption of different theoretical orientations by researchers examining ICSE at different levels of analysis, a lack of contextual positioning, as well as poor methodological rigor. Originality/value: Based on the findings, the authors introduce a multilevel and multidisciplinary conceptual framework that integrates the concepts of emotional intelligence (EI) and intercultural communication competence (ICC) as the key variables that explain trust development during the interaction between two key culturally different stakeholders: service providers (employees) and service receivers (customers). Finally, the authors discuss the contributions and implications for both academics and practitioners.
Keywords: Emotional intelligence; Intercultural communication competence; Intercultural service encounter; Systematic review